A simple PAN-based fabrication method for microstructured carbon electrodes for organic field-effect transistors. (June 2015) - Jung, Chan-Hee; Kim, Wan-Joong; Jung, Chang-Hee; Hwang, In-Tae; Khim, Dongyoon; Kim, Dong-Yu; Lee, Jae-Suk; Ku, Bon-Cheol; Choi, Jae-Hak
Abstract: Facile and efficient fabrication of polyacrylonitrile (PAN)-based conductive graphitic carbon microstructures (GCMs) and their application to the electrodes of organic field-effect transistors (OFETs) is described. The PAN thin films spin-coated on a SiO2 -deposited Si wafer was irradiated through a pattern mask with 150 keV H + ions at various fluences, and subsequently developed to form PAN microstructures. The resulting PAN microstructures were carbonized at various temperatures to create the GCMs. The analytical results revealed that the optimized fluence and carbonization temperature for well-defined GCMs was 3 × 10 15 ions cm −2 and 100 °C, respectively, and that the resulting GCMs created at the optimized condition exhibited a greatly low surface roughness of 0.36 nm, a good electrical conductivity of about 600 S cm −1, and a high work function of 5.11 eV. Noticeably, the GCM electrodes-based p-type OFET showed a comparable performance to that of the gold electrode-based one, demonstrating that the practical use of GCMs as cheap electrodes to replace expensive metallic ones for organic electronic devices.